A new leaf-litter harvestman species of the genus Karos (Opiliones: Stygnopsidae: Karosinae), with a reanalysis of the morphological phylogeny of the genus - Cruz-López, Jesús A. (Zootaxa, 2018)
Karos Goodnight & Goodnight, 1944 is the most diverse genus of the family Stygnopsidae. It contains seven micro-endemic species from the Huasteca region in eastern Mexico. In this paper, the new species Karos morronei sp. nov. is described based on the morphology of adults of both sexes. The new species is from Zacualtipán de Ángeles, Hidalgo State, which represents the southernmost record for the genus. Additionally, a reanalysis of the previous morphological phylogeny of the genus using both parsimony and maximum likelihood methods is provided. According to the morphological reanalysis, K. morronei sp. nov. exhibits an autapomorphy (males with femur IV thicker than females) and is the sister group of the clade that includes K. barbarikos, K. hexasetosus, K. monjarazi, K. parvus and K. singularis. Finally, information of barcoding (CO1) is provided for this new species.